Sex Differences in the Occurrence of Major Clinical Events in Elderly People with Type 2 Diabetes Mellitus Followed up in the General Practice - Al-Salameh, Abdallah; Bucher, Sophie; Bauduceau, Bernard; Benattar-Zibi, Linda; Berrut, Gilles; Bertin, Philippe; Corruble, Emmanuelle; Danchin, Nicolas; Derumeaux, Geneviève; Doucet, Jean; Falissard, Bruno; Forette, Françoise; Hanon, Olivier; Ourabah, Rissane; Pasquier, Florence; Pinget, Michel; Becquemont, Laurent; Ringa, Virginie (Experimental and Clinical Endocrinology & Diabetes, 2020)
Aims The main aim of the present work was to assess if sex influences the occurrence of major clinical events in elderly people with type 2 diabetes followed up in the primary care.Methods 983 subjects aged ≥65years with type 2 diabetes were included by 213 general practitioners and followed up prospectively for three years. Major clinical events were recorded every six month. The first endpoint was a composite of all-cause death and major vascular events (acute coronary syndrome, non-fatal stroke or transient ischemic attack, or revascularization for peripheral artery disease). The second endpoint was all-cause hospitalization. The occurrence of each endpoint was analyzed in order to estimate the role of sex and determine other predictors of major clinical events.Results At baseline, women were older than men but they had a lower prevalence of coexisting diseases (cardiovascular disease and cancer) and equivalent diabetes control (Glycated hemoglobin A1C: 6.9%±0.9 vs. 7.0%±1.1). Over the follow-up period, women were at lower risk to develop the composite endpoint (HR 0.60, 95% CI 0.40-0.91, p=0.016) and the hospitalization endpoint (OR 0.71, 95% CI 0.52-0.96, p=0.029). Coexisting diseases, functional ability and concomitant medications emerged as significant predictors of both endpoints.Conclusions Elderly women with well-controlled type 2 diabetes were less likely to experience major clinical events than their male counterparts. More studies are needed to determine the reasons for the higher hospitalization rate in men.
Keywords: Type 2 Diabetes Mellitus; sex- and gender-related differences; elderly; mortality; cardiovascular disease; hospitalization; primary care